IoT Sistem Monitoring Dan Kontroling Kelembaban Tanah Pada Tanaman - Nanang Budi Pasetyo; Rini Indriati; Rina Firliana (Universitas Katolik Widya Karya Malang, 2024)
Modern agriculture increasingly relies on technology to increase efficiency and productivity, so that humans nowadays always need tools that can make their work easier, especially for monitoring soil moisture. in presenting a soil moisture control monitoring system tool, which can be used by the community for efficient gardening. Where the system uses microcontroller technology which has been developed internationally. The creation of this system aims to make gardening easier. From the case studies raised in this research, the lack of efficient soil moisture affects plant growth. A system was created to produce a tool for controlling and monitoring soil moisture conditions in waterfall method plants. The stages of this research include analysis, system design, implementation, testing and maintenance. The implication of this research is the optimization of the gardening process by farmers in maintaining soil moisture by automatically turning on and turning off buttons. This system is based on IoT which is a soil moisture sensor using a soil moisture sensor & I2C LCD as a monitoring tool. It is said that the soil is damp if the water content is 60% -80%, if it is less than this then the water pump will turn on automatically.